FAKTOR TINGKAT KEMAHALAN HARGA SAHAM, KINERJA KEUANGAN PERUSAHAAN DAN KEPUTUSAN PEMECAHAN SAHAM (STOCK SPLITS): APLIKASI ANALISIS DISKRIMINAN - Khomsiyah Khomsiyah; Sulistyo Sulistyo (Journal of Indonesian Economy and Business (JIEB), 2001)
This paper applied the discriminant analysis to examine whether the corporate  financial performance and share overprices provide information about stock split decision. We used earnings price ratio and earnings growth as a proxy of corporate financial performance and price earnings ratio and price to book value as a proxy of share overprices. We also detected the assumptions underlying application of the discriminant analysis. A hundred and fifteen listed companies of The Jakarta Stock Exchange are selected as the unit of analysis. The result of this study indicates that splitting firms differ from non-splitting firms by price earning ratio and earning per share factors.